Find out the value of x and y xy=6 2x-y=3 ???

Thanks in advance !

1 Answer
Oct 12, 2017

If would use substitution. If we rearrange the second equation for y, we get;

2x - 3 = y

Accordingly:

x(2x -3) = 6

2x^2 - 3x - 6 =0

By the quadratic formula, we get:

x = (-(-3) +- sqrt(3^2 - 4 * 2 * -6))/(2 * 2)

x= (3 +-sqrt(57))/4

We can now solve for y.

y = 2((3 + sqrt(57))/4) - 3

y = (3 + sqrt(57) - 6)/2

y = (sqrt(57) - 3)/2

Now for the other solution, we get:

y = (-sqrt(57) - 3)/2

So our solutions are ((3 - sqrt(57))/4, (-sqrt(57) - 3)/2) and ((3 + sqrt(57))/4, (sqrt(57) - 3)/2)

Hopefully this helps!